Perancangan Sistem Informasi Imunisasi di Poliklinik Anak RS Bhayangkara TK I Pusdokkes POLRI - Dian Utami Oktaviana; Erix Gunawan (Publikasi Indonesia, 2022)
According to the World Health Organization (WHO), in 2018 there were around 20 million children in the world who didn’t get complete immunization, some even didn’t get immunized. In fact, obtaining community immunity (herd immunity) requires high immunization coverage (at least 95%) and is evenly distributed. Therefore, at this time to support the government's program in implementing child immunization, the concentration is needed by all health service facilities, as well as at Bhayangkara TK I Pusdokkes Polri Hospital as a military and police hospital which is assigned the task of supporting the program. For this reason, Bhayangkara TK I Pusdokkes Polri Hospital built an information system, particularly in the children's polyclinic to support and facilitate the implementation of child immunization. to develop this software using SDLC (Software Development Life Cycle) modeling. With this information system, it is hoped that it will assist in the availability of valid and transparent information for the community, especially parents, and officers to facilitate data management regarding immunization such as determining doctor's schedules, reporting, and printing children's immunization certificates.